Relations between attachment insecurity and role and outcome expectations for couple therapy. Issue 1 (13th August 2020) - Muetzelfeld, Hannah; Megale, Allison; Friedlander, Myrna L.; Xu, Mengfei
Abstract : With the efficacy of couple therapy no longer in doubt, researchers are seeking to identify client characteristics that explain variability in retention and outcomes. We examined the link between two self‐reported characteristics, attachment insecurity and treatment expectations (for self, partner, and outcome), in a Mechanical Turk sample of 182 adults in committed relationships. A significant canonical correlation accounted for 27 per cent of the variance between the two sets of variables. Interpretation of the structure coefficients indicated that (1) low role expectations for one's partner were predicted by high attachment anxiety; (2) low expectations for the outcome of couple therapy were predicted by high attachment avoidance coupled with low attachment anxiety; and (3) high self and outcome expectations were predicted by high attachment anxiety when attachment avoidance was low. We discuss the implications of these results for engaging couples with insecure attachment patterns. Practitioner points: Expectations for couple therapy are measurable, and related to levels of attachment insecurity Results of this study underscore the importance of clinicians inquiring early on in treatment about what each partner anticipates about the process of couple therapy Clinicians should work gently and creatively with clients with low expectations to help them safely engage in the treatment process Recognising attachment insecurity should be a signal to clinicians to monitor relevant attachment behaviours and related expectations 抽象: 依恋不安全感与夫妻治疗角色和效果期望的关系 随着夫妻治疗的有效性不再受到怀疑，研究者正在寻找能够解释治疗维持和结果中的变化的来访者特征。我们研究了两个自我报告的特征之间的联系，即依恋不安全感和治疗期望（对自我、伴侣和结果的期望），样本为土耳其机器人（Mechanical Turk）抽样的182个处于确定关系中的成年人。两组变量之间的方差中，显著的典型相关占27%。结构系数的阐释表明：（1）高依恋焦虑可预测对伴侣的低角色期望；（2）高依恋回避加上低依恋焦虑可预测夫妻治疗结果的低期望；（3）当依恋回避水平较低时，高依恋焦虑可预测高自我期望和结果期望。我们讨论了这些结果对不安全依恋模式的夫妇的影响。 从业者启示: 对夫妻治疗的期望值是可测量的，并且与依恋不安全程度相关 这项研究的结果强调了治疗师在治疗早期询问每个伴侣对夫妻治疗过程的预期的重要性 治疗师应对期望值较低的来访者采取柔和并创造性的工作方式，帮助他们安全参与治疗过程 认识到依恋不安全应该是治疗师关注相关依恋行为和有关期望的信号 Resumen: Relaciones entre la inseguridad del apego y las expectativas de roles y resultados en terapia de pareja Ahora que la eficacia de la terapia de pareja ya no está en duda, los investigadores buscan identificar las características del cliente que explican la variabilidad existente tanto en la retención como en los resultados. En el presente estudio, examinamos el vínculo entre dos características auto‐informadas, la inseguridad del apego y las expectativas de tratamiento (para sí mismo, para el otro miembro de la pareja y para el resultado de la terapia), en una muestra de Mechanical Turk de 182 adultos en relaciones de pareja. Una correlación canónica significativa explicó el 27% de la varianza entre los dos conjuntos de variables. La interpretación de los coeficientes hallados indicó que (1) una alta ansiedad en el apego propio predice las bajas expectativas de rol para el otro (miembro de la pareja; (2) un nivel alto de apego evitativo junto con baja ansiedad de apego predicen el resultado de la terapia de; y (3) una alta ansiedad de apego cuando la evitación del apego era baja, predice altas expectativas sobre el resultado de la terapia y sobre uno mismo. Se discuten las implicaciones de estos resultados para las relaciones con parejas con patrones de apego inseguros. Puntos implicación práctica: Las expectativas de la terapia de pareja son mensurables y están relacionadas con los niveles de inseguridad del apego. Los resultados de este estudio subrayan la importancia de que los terapeutas pregunten desde el principio del tratamiento sobre lo que anticipa cada pareja acerca del proceso de la terapia de pareja. Los terapeutas deben trabajar con amabilidad y creatividad con los clientes que traen bajas expectativas, para ayudarles a participar de manera segura en el proceso de tratamiento. Reconocer la inseguridad del apego debe ser una señal para que los terapeutas monitoricen los comportamientos de apego relevantes y las expectativas relacionadas.